Location, Infrastructure, Promotion: Determining Factors of Tourism-Driven Income Growth in Dua Island - Samsul Rizal; Nargiza Pirimova (Cahaya Ilmu Cendekia Publisher, 2025)
Purpose of the study: This study aims to analyze the influence of three key tourism development variables location, infrastructure, and promotion on increasing community income in the Dua Island area, East Bakongan, South Aceh. A central objective is to identify which of these factors exerts the most significant impact on local economic improvement. Methodology: Employing a quantitative explanatory approach, this research collected primary data through a survey method. A structured questionnaire was distributed to 92 respondents engaged in tourism-related activities around Dua Island. Data analysis was performed using multiple linear regression with IBM SPSS Statistics 23. Classical assumption tests (normality, multicollinearity, heteroscedasticity) were conducted prior to hypothesis testing via t-test (partial) and F-test (simultaneous). Main Findings: The results confirm that location, infrastructure, and promotion each have a positive and significant partial effect on local community income. The analysis identifies promotion as the most dominant influencing variable. Simultaneously, the three variables collectively have a significant positive impact on income (F-count = 43.57 > F-table), with the model explaining a substantial proportion of the variance in economic outcomes. Novelty/Originality of this study: This study offers novel insights by integrating an Islamic economic perspective (maslahah/public benefit) into the analysis of tourism-led rural development. Its primary contribution lies in empirically demonstrating the hierarchical influence of development factors within a small-island context, providing evidence that strategic promotion, coupled with accessibility and infrastructure, is crucial for optimizing tourism's economic benefits for local communities in emerging coastal destinations.